2006
DOI: 10.1113/jphysiol.2005.104612
|View full text |Cite
|
Sign up to set email alerts
|

Renal vasoconstrictor responses to static exercise during orthostatic stress in humans: effects of the muscle mechano‐ and the baroreflexes

Abstract: Renal circulatory adjustments to stress contribute to blood pressure and volume regulation. Both handgrip (HG) and disengagement of baroreflexes with lower body negative pressure (LBNP) can engage the sympathetic nervous system (SNS). However, the effect of simultaneous HG and LBNP on the renal circulation in humans is not known. Eighteen young healthy volunteers were studied. Beat-to-beat changes in renal blood flow velocity (RBV; Duplex Ultrasound), mean arterial pressure (MAP; Finapres) and heart rate (ECG)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 29 publications
(36 reference statements)
1
13
0
Order By: Relevance
“…Previous reports showed that LBNP > ¡20 mmHg unloads both low and high pressure baroreceptors and activates sympathetic system (Jacobsen et al 1993;Khan et al 2002). In addition, other reports (from this laboratory and others) showed increased plasma norepinephrin (Momen et al 2006) and increased renal norepinephrin outXow during LBNP > ¡20 mmHg (Tidgren et al 1990). Thus, it is considered Fig.…”
Section: Renal Blood Xow Velocity and Renal Vascular Resistancementioning
confidence: 80%
See 2 more Smart Citations
“…Previous reports showed that LBNP > ¡20 mmHg unloads both low and high pressure baroreceptors and activates sympathetic system (Jacobsen et al 1993;Khan et al 2002). In addition, other reports (from this laboratory and others) showed increased plasma norepinephrin (Momen et al 2006) and increased renal norepinephrin outXow during LBNP > ¡20 mmHg (Tidgren et al 1990). Thus, it is considered Fig.…”
Section: Renal Blood Xow Velocity and Renal Vascular Resistancementioning
confidence: 80%
“…One subject was excluded from the analysis of this protocol because it was not possible to get blood pressure recordings of good quality from the Wnger. According to previous studies from this laboratory during the IFHG there is a sympathetically mediated renal vasoconstriction mainly due to stimulation of the sensory Wbers within the exercising muscle (Momen et al 2003(Momen et al , 2006.…”
Section: Protocol a Isometric Fatiguing Handgrip (Ifhg)mentioning
confidence: 95%
See 1 more Smart Citation
“…The rapid sympathetic nerve responses are hardly explained by the muscle mechanoreflex. Momen et al (31,32) recently reported that a 15-s bout of evoked static muscle contraction by percutaneous electrical stimulation increased renal vascular resistance in humans, suggesting that muscle mechanoreflex engagement was responsible for the increase in renal vascular resistance. Taken together, the muscle mechanoreflex may not work on the whole vascular system but may affect the renal vascular bed particularly.…”
Section: Central Command But Not the Muscle Mechanoreflex Is Responmentioning
confidence: 99%
“…Several integrative physiology studies have shown that some vascular beds vasoconstrict and some vasodilate in responses to different stressors. [20][21][22] Following salt loading, if vasodilatation in visceral vasculature is sufficient to maintain BP homeostasis, cutaneous vasodilatation should be unnecessary and any decrease in Tre would be minimal. However, our results suggest that vasodilation did occur in the cutaneous vasculature.…”
Section: Between Groups (Independent T-test)mentioning
confidence: 99%